2022
DOI: 10.3390/neurolint14040070
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-Month Results from a Prospective Clinical Study Evaluating the Efficacy and Safety of Cellular Bone Allograft in Subjects Undergoing Lumbar Spinal Fusion

Abstract: Background: While autologous bone grafts remain the gold standard for spinal fusion procedures, harvesting autologous bone is associated with significant complications, including donor site infection, hematomas, increased operative time, and prolonged pain. Cellular bone allograft (CBA) presents an alternative to autologous bone harvesting, with a favorable efficacy and safety profile. The current study further investigates CBA as an adjunct to lumbar spinal fusion procedures. Methods: A prospective, multicent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Seven studies evaluated the cervical spine, 17-19,21,22,24,27 and eleven evaluated outcomes of the lumbar spine. 14-16,20,23,25,26,28-31 One study did not longitudinally follow patients but provided a case series of patients presenting with complications of a specific lot of FiberCel cellular bone matrix. 9
Figure 1.PRISMA Flowchart.
…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies evaluated the cervical spine, 17-19,21,22,24,27 and eleven evaluated outcomes of the lumbar spine. 14-16,20,23,25,26,28-31 One study did not longitudinally follow patients but provided a case series of patients presenting with complications of a specific lot of FiberCel cellular bone matrix. 9
Figure 1.PRISMA Flowchart.
…”
Section: Resultsmentioning
confidence: 99%
“…When comparing our fusion rates with published literature, our fusion rates are similar. Wind et al 14 reported a series of 201 patients undergoing lumbar spinal fusion through various surgical approaches with Trinity Elite, with an overall fusion rate of 90.5% as assessed radiographically by review of dynamic radiographs and CT scans. Of this sample, only 13 patients were treated with posterolateral lumbar fusion, in which they reported a fusion rate of 92.3%; the remainder of the patients relied on interbody fusion rather than posterolateral fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Trinity Elite, developed by Orthofix Medical Inc, is one such cellular-based autograft (CBA) consisting of viable cancellous bone with demineralized cortical bone and osteogenic cells. Trinity in patients undergoing foot and ankle arthrodesis with comorbidities provide comparable or greater fusion rates than autograft, 7 , 8 and both animal model 6 , 9 and limited clinical studies have shown that it can be safely used for fusions involving the cervical 10 , 11 and lumbar 12 13 14 spine. However, limited evidence exists directly comparing fusion rates with Trinity with other bone graft alternatives.…”
mentioning
confidence: 99%
“…[13][14][15] Collectively, these features provide all the grafting elements necessary for a successful bone/joint fusion. 16 Studies have shown the clinical advantage of CBAs in lumbar and cervical surgical procedures while eliminating the risk associated with autograft harvesting. 16,17 However, there is currently limited information on the efficacy and safety of CBA with foot/ankle arthrodesis, especially in pa-tients with risk for non-union.…”
Section: Introductionmentioning
confidence: 99%
“…16 Studies have shown the clinical advantage of CBAs in lumbar and cervical surgical procedures while eliminating the risk associated with autograft harvesting. 16,17 However, there is currently limited information on the efficacy and safety of CBA with foot/ankle arthrodesis, especially in pa-tients with risk for non-union. This study aims to evaluate the rate of fusion and complications in patients who underwent foot/ankle arthrodesis procedures using a CBA.…”
Section: Introductionmentioning
confidence: 99%